PROSES MORFOFONEMIK DALAM BAHASA INGGRIS DAN BAHASA BALI (SUATU ANALISIS KONTRASTIF) - GUNAWAN, I MADE YUDHI; KODONG, FENTJE; LASUT, THERESIA M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research is set to identify, analyze, and describe the morphophonemic processes and its types in both English and Balinese language, as well as uncovering the similarities and differences of morphophonemic processes in both languages. This research analyzes and describes the morphophonemic processes in both languages according to the theory of morphophonemic rules by Jensen (1990). The required data is collected from various sources. The English data were collected from various English books and dictionaries, and the Balinesse data were collected from various sources as well. However, the Balinese data were collected mainly from the informants in Werdhi Agung village in Bolaang Mongondow regency. Other additional sources were collected from previous research and articles in Balinese, as well as various books of Balinese. For example: Struktur Bahasa Bali (1981) by Bawa, W et al, Geografi Dialek Bahasa Bali (1981) by Herusantosa et al, Kamus Bali - Indonesia (1985) by Bagus, G et al, and other books as well. Other data were sourced from recorded audio-visual dialogs in Balinese traditional plays and wayang puppet show. This research uncovers some similarities and differences in morphophonemic processes of English and in Balinese. There are ten kinds of morphophonemic rules, according to Jensen (1990). The processes are assimilation, dissimilation, insertion, deletion, haplology, metathesis, vowel harmony, vowel reduction, tone rules, and morpheme sequence rules. In English, most processes are present, except vowel harmony and tone rules. In Balinese, most of those aforementioned processes are also present, except metathesis and tone rules. Keywords: Morphophonemic Process, English Language, Balinese Language, Contrastive Analysis.